Providing Grounds for Trust: Developing Conceptual Requirements for the Long-Term Preservation of Authentic Electronic Records - MacNeil, Heather (Archivaria, 2000)
Since 1999, the International Research in Permanent Authentic Recordsin Electronic Systems (InterPARES) Project has been investigating the issues associated with the long-term preservation of authentic electronic records. The identification ofconceptual requirements for the verification of authentic electronic records is the responsibility of the InterPARES Authenticity Task Force. The work of the task force is being carried out in three stages: (1) identifying and defining, using contemporary archival diplomatics, the elements of an electronic record that are relevant to a consideration of its authenticity; (2) testing the validity of the elements through cases tudies of electronic systems; and (3) developing general and specific requirements for the preservation of authentic electronic records over the long term. This article reportson the work accomplished by the task force to date in each of the three stages. RÉSUMÉ Depuis 1999, le projet InterPARES (International Research on Permanent Authentic Records in Electronic Systems) se penche sur les problèmes reliés à la conservation à long terme de documents électroniques authentiques. La formulation des exigences conceptuelles nécessaires à la vérification de l’authenticité des documents électroniques est sous la responsabilité du groupe de travail sur l’authenticité. Celui-ci a divisé ses tâches en trois étapes: (1) identifier et définir, enutilisant la diplomatique archivistique contemporaine, les éléments d’un document électronique qui sont liés à son authenticité; (2) vérifier la validité de ces éléments aumoyen d’études de cas de systèmes électroniques; et, (3) développer des exigencesgénérales et spécifiques pour la conservation à long terme de documents électroniquesauthentiques. Cet article présente le travail qui a été accompli jusqu’à présent par le groupe de travail dans chacune de ces trois étapes.